The narrative accounts of recovering drug users - Adams, Chantal (Centre for Social Science Research(CSSR), 2024)
This study aims to provide pertinent information regarding the widespread use of methamphetamine occurring in South Africa. This study explores how individuals who were addicted to crystal methamphetamine (CM) create meaning of their experiences of addiction and recovery. Since most studies regarding CM use provide a quantitative focus this study provides a socially and culturally informed account of the subjective experiences of CM addiction. The researcher obtained access to a community-based organisation for recovering addicts and the snowball method of sampling was used to recruit 11 research participants. Participants were interviewed about their experiences of recovery and ethnographic field notes were written about the researcher's observations of and participation in the support group. The data were analysed using a narrative approach. This study adds to the current literature in the field of addiction. It particularly found that religion plays in integral role in assisting those recovering from the use of CM. The findings suggest that the experience of addiction and recovery is unique and that it occurs within a particular context that is continually evolving.